2018
DOI: 10.1016/j.juro.2018.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Cyst Rupture during Partial Nephrectomy for Cystic Renal Masses—Does it Increase the Risk of Recurrence?

Abstract: Intraoperative cyst rupture during partial nephrectomy is a relatively common occurrence but with few oncologic implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 26 publications
1
23
2
Order By: Relevance
“…up to 100 months postoperatively. 20 A prior study by Spaliviero et al involving 284 laparoscopic partial nephrectomy cases echoed a similar phenomenon, whereby only one retroperitoneal recurrence was reported 14 months postoperatively despite the negative margins and absence of intraoperative cyst rupture in all cases. 21 The study by Chen et al also highlighted that only four of nine patients with recurrence were reported to have cyst rupture, and no association can be derived between cyst rupture with the site of recurrence (p=1.00).…”
Section: Case Reportmentioning
confidence: 69%
“…up to 100 months postoperatively. 20 A prior study by Spaliviero et al involving 284 laparoscopic partial nephrectomy cases echoed a similar phenomenon, whereby only one retroperitoneal recurrence was reported 14 months postoperatively despite the negative margins and absence of intraoperative cyst rupture in all cases. 21 The study by Chen et al also highlighted that only four of nine patients with recurrence were reported to have cyst rupture, and no association can be derived between cyst rupture with the site of recurrence (p=1.00).…”
Section: Case Reportmentioning
confidence: 69%
“…In surgery for cystic renal tumors, inadvertent cyst rupture and tumor spillage should be avoided. Although the risk of dissemination owing to intraoperative cyst rupture is controversial, 16,17 Santiago et al 18 . and Limb et al 19 .…”
Section: Discussionmentioning
confidence: 99%
“…In surgery for cystic renal tumors, inadvertent cyst rupture and tumor spillage should be avoided. Although the risk of dissemination owing to intraoperative cyst rupture is controversial, 16,17 Santiago et al 18 and Limb et al 19 reported that intraoperative cyst puncture did not affect oncological outcomes. Meanwhile, Hayakawa et al 20 reported that the cyst fluid cytology in cystic RCC had a positive rate of 16.7%.…”
Section: Discussionmentioning
confidence: 99%
“… 1 As the malignant tumours rupture, cancer cells metastasize in the abdominal cavity, patients face a high risk of recurrence. 2 Meanwhile, studies have shown that more functional nephrons correlate with a better prognosis of patients. 3 Therefore, it is crucial to achieving accurate and complete tumour resection during partial nephrectomy (PN).…”
Section: Tablementioning
confidence: 99%
“…Caiguang Cao 1,2,* Shaohui Deng 3,* Binshuai Wang 3,* Xiaojing Shi 1,2 Liyuan Ge 3 Min Qiu 3 Fan Zhang 3 Min Lu 4 Lulin Ma 3 Chongwei Chi 1 Zhenhua Hu…”
Section: A C K N O W L E D G E M E N T Smentioning
confidence: 99%